2013
DOI: 10.1371/journal.pone.0074608
|View full text |Cite
|
Sign up to set email alerts
|

Tonic and Phasic Smooth Muscle Contraction Is Not Regulated by the PKCα - CPI-17 Pathway in Swine Stomach Antrum and Fundus

Abstract: Regulation of myosin light chain phosphatase (MLCP) via protein kinase C (PKC) and the 17 kDa PKC-potentiated inhibitor of myosin light chain phosphatase (CPI-17) has been reported as a Ca2+ sensitization signaling pathway in smooth muscle (SM), and thus may be involved in tonic vs. phasic contractions. This study examined the protein expression and spatial-temporal distribution of PKCα and CPI-17 in intact SM tissues. KCl or carbachol (CCh) stimulation of tonic stomach fundus SM generates a sustained contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Based on this large body of data showing spatial‐temporal redistribution of PKC from the cytosol to the plasma membrane occurs with activation in isolated SMCs, investigators infer that this also occurs and is a (the) mechanism whereby PKC‐CPI‐17 regulates MLCP activity in intact SM tissues (i.e., PKC is a cytosolic protein that, upon tissue activation, translocates to the plasmalemma where it is activated and then translocates back to the cytosol where it activates CPI‐17 which decreases MLCP activity and thus affects MLC 20 phosphorylation levels). In contrast to this, we have reported that PKCα has a preferential peripheral localization at the plasma membrane in unstimulated SMCs in tissues and this does not change with agonist activation (Zhang et al, ) and (Fig. ).…”
mentioning
confidence: 68%
“…Based on this large body of data showing spatial‐temporal redistribution of PKC from the cytosol to the plasma membrane occurs with activation in isolated SMCs, investigators infer that this also occurs and is a (the) mechanism whereby PKC‐CPI‐17 regulates MLCP activity in intact SM tissues (i.e., PKC is a cytosolic protein that, upon tissue activation, translocates to the plasmalemma where it is activated and then translocates back to the cytosol where it activates CPI‐17 which decreases MLCP activity and thus affects MLC 20 phosphorylation levels). In contrast to this, we have reported that PKCα has a preferential peripheral localization at the plasma membrane in unstimulated SMCs in tissues and this does not change with agonist activation (Zhang et al, ) and (Fig. ).…”
mentioning
confidence: 68%
“…However, PKC may be localized in the cell periphery in both resting and stimulated tissues. Immunohistochemical studies have shown that the distribution of PKCα in the longitudinal and circular layers of the swine stomach tonic fundus and phasic antrum under resting conditions does not differ, being predominantly localized near the smooth muscle plasma membrane, and stimulation of either tissue with PDBu or carbachol does not alter this peripheral PKCα distribution (Zhang et al, 2013). Also, PKC is found in other cell compartments like the mitochondria and soluble fraction of cells subjected to oxidative stress, a known activator of PKC (Konishi et al, 2001; Steinberg, 2015).…”
Section: Pkc Distribution and Translocationmentioning
confidence: 99%
“…The functional pleiotropy of CPI-17 may explain why CPI-17 signaling is silenced in the larger arteries, smooth muscle from genetically hypertensive rats and from other organs and models (90, 109,110,111,112). The multi-functionality may be a common feature of the endogenous regulator proteins for kinases/phosphatases, such as DARPP32, phosphatase inhibitor-1, inhibitor-2, a Raf kinase inhibitor protein (RKIP), and cyclin-dependent kinase inhibitors (p21CIP/WAF, p27KIP1, and p57) (113,114,115,116,117,118,119,120,121,122,123).…”
Section: Paradigms and Paradoxes In Ca2+-sensitization Researchmentioning
confidence: 99%